The Interaction Between Ethical Standards of Counsellors and their Legal Responsibility - Frazier, Dorothy M. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper seeks to investigate an area of potential conflict concerning the counselling profession. Specifically, (1) the professional ethics recognized by counsellors, and (2) the differing legal responsibilities imposed by law on members of the profession with respect to clients and to members of society at large (to the profession itself). It is the writer's thesis that in the implied contract between counsellor and counsellee there must be maintained a standard of conduct which is determined in part by professional ethics and in part by judicial decision. The author surveyed the English language literature on ethical standards, confidentiality and professional responsibility along with the American and Canadian reported decisions on legal liability. The author favors legislative recognition of the profession and provincial licensing of entry into the profession as a means of lessening the risk of conflict between the guidelines incorporated in informal codes of ethics and the objective standards set by the courts. The author does not attempt to answer the questions raised in this investigation but rather hopes to reveal by these questions the conflicts which arise in the areas of ethical standards and legal responsibility.